Pomalidomide plus low-dose dexamethasone in patients with relapsed/refractory multiple myeloma and moderate renal impairment: a pooled analysis of three clinical trials. Issue 12 (1st December 2016) - Siegel, David S.; Weisel, Katja C.; Dimopoulos, Meletios A.; Baz, Rachid; Richardson, Paul; Delforge, Michel; Song, Kevin W.; San Miguel, Jesus F.; Moreau, Philippe; Goldschmidt, Hartmut; Cavo, Michele; Jagannath, Sundar; et al.
Abstract: Renal impairment (RI) is a major comorbidity in patients with multiple myeloma (MM). Here we present the pooled safety and efficacy analysis of three clinical trials (MM-002, MM-003, and MM-010) of pomalidomide + low-dose dexamethasone (POM + LoDEX) in patients with moderate RI (creatinine clearance [CrCl] ≥ 30 to <60 mL/min) and without RI (≥ 60 mL/min). Trial protocols were approved by the institutional review board of each site involved. Patients with RI were older than patients without RI, although other baseline characteristics were similar. The dosing and safety profile of POM + LoDEX was similar across RI subgroups. Median overall response rate, progression-free survival, time to progression, and duration of response were not significantly different between RI subgroups. However, patients with vs. without RI had significantly shorter median overall survival (10.5 vs. 14.0 months, respectively; p  = .004). This analysis demonstrates that POM + LoDEX is a safe and effective treatment for patients with moderate RI. The trials were registered at ClinicalTrials.gov as NCT00833833 (MM-002), NCT01311687 (MM-003), and NCT01712789 (MM-010) and at EudraCT as 2010-019820-30 (MM-003) and 2012-001888-78 (MM-010).